Personality congruence in married couples - Marušić, Iris (Array, 1998)
Numerous studies have provided evidence for spouse similarity on a number of traits. Assortative mating has thus been documented for various physical characteristics, socioeconomic and demographic variables, cognitive abilities and personality traits. However, there is little evidence suggesting assortative mating effect on a level of broad personality dimensions. The purpose of this study was to examine personality congruence in married couples on dimensions of the five-factor model. NEO PI-R was administered on 110 married couples. The age of husbands ranged from 35 to 61 years, with the average of 48, while the age of wives ranged from 37 to 55, with the average of 45 years. Few significant correlations were obtained on both domain and facet level, all positive in direction. On a domain level, significant spouse correlations were found for Openness ( r = .26, p < .01) and Agreeableness (r = .23, p < .01). On a facet level, significant correlations were found for the Self-Consciousness facet of N, Modesty facet of A, and Actions and Values facets of O. The correlations obtained on a facet level are in the range of those on a domain level, except the one for Values facet ( r = .38, p<.01). Our results are thus in accordance with the previous findings documenting positive assortative mating for personality traits. Furthermore, they add to the evidence suggesting that, within the five-factor model, the largest spouse similarity exists for the Openness to Experience.